TERAPI GANGGUAN SOMATOFORM - Sulistiana Dewi (Nusantara Hasana Journal, 2026)
Somatoform disorder is a group of mental health disorders characterized by persistent and recurrent physical symptoms that cannot be fully explained by an underlying medical condition. This condition often causes significant psychological distress, reduced quality of life, and increased utilization of healthcare services. The management of somatoform disorder aims to reduce symptoms, improve psychosocial functioning, and help patients understand the relationship between psychological factors and physical complaints. This paper discusses various therapeutic approaches used in the treatment of somatoform disorders through a literature review of scientific publications. The findings indicate that Cognitive Behavioral Therapy (CBT) is the most effective intervention for reducing symptom severity and health-related anxiety. In addition, psychodynamic therapy, mindfulness-based interventions, patient education, and collaborative care involving physicians and mental health professionals have demonstrated significant benefits. Pharmacological treatment may be considered in patients with comorbid conditions such as depression or anxiety disorders. A comprehensive, patient-centered therapeutic approach has been shown to improve quality of life and reduce patients’ dependence on repeated medical examinations. Therefore, early detection and appropriate management are essential to achieve optimal therapeutic outcomes in patients with somatoform disorders.